Розробка зносостійких наплавлених шарів із порошкових дротів для підвищення ресурсу роботи лопаток колеса млинового вентилятора - Войтович, Андрій; Головчук, Мирослав (Видавництво Львівської політехніки, 2013)
The aim of the work is to conduct a comparative analysis of durability of the over welded layers with four commercially available boron-containing cored wires (150B6Tі10, 150Cr10B2VМn, 90Cr12SiB, 70Cr20B3Ti). All investigated coatings have been developed in order to increase the operating time and to reduce the maintaince period of the mashine parts that operate under the conditions of the severe abrasive wear. The microstructure and microhardness of the layers have been investigated on the cross-sections. A resistance against abrasion wear has been tested by an operating temperature of 150 °C and the velocity of abrasive particles (200 μm sand) of 36 m/s. It was found that the average hardness of the clad layers due to the formation of the carbides and borides rises to the values of 642 – 1028 HV0.2. The highest values were measured for 150Cr10B2VМn layers and the lowest – for 150B6Tі10 layers. The last can be explained by the formation of the crack network in the hard boron rich matrix. The maximal abrasion wear resistance was observed for the layers with a matrix with austenitic microstructure and carbide inclusions. The best 150B6Tі10 coatings demonstrate an increase in abrasion resistance more than twice if to compare with a substrate 10CrSiNiMn material.
Keywords: over weld; cored wire; electric arc welding; abrasion wear resistance; austenitic matrix; hard phase inclusions